A EMPIRICAL STUDY ON RISK AND RETURNS OF HDFC AND ICICI BANKS - Dr. B. G. Prasanthi, Dr. B. G. Lakshmi, Dr. Mini.K.Abraham, Maha Lakshmi A.L. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Many times the investors go on acquiring assets in an adhoc and unplanned manner . The result is at high risk, low return profile that they may face. All such assets of financial nature such as gold, silver, realestate, building, insurance policies, post office certificate. NSC or NSS would constitute his portfolio & the wise investor not only plans his portfolio as per risk return profile or preferences but manages his portfolio efficiently so as to secure the highest return for the lowest risk possible at that level of investment. This is in short the portfolio management. The basic principle is that the higher the risk, the higher is the return &investor should have clear perception of elements of risk & return when he makes investments. Risk return analysis is essential for the investment & portfolio management. An investor considering investment is securities is faced with the problem of choosing from among a large no. of securities. His choice depends upon the risk return characteristics of individual securities. He would attempt to choose the most desirable securities & like to allocate his funds over group of securities. As the economic and financial environment keep changing the risk return characteristics of individual securities as well as portfolios also change. A portfolio is a collection of assets. The assets may be physical or financial like Shares, Bonds, Debentures, Preference Shares, etc. The individual investor or a fund manager would not like to put all his money in the shares of one company, that would amount to great risk. He would therefore, follow the age old maximum that one should not put all the eggs into one basket. By doing so, he can achieve objective to maximize portfolio return and at the same time minimizing the portfolio risk by diversification.